(untitled) (Global Journal of Science Frontier Research, 2012)
The environmental impact and seasonal variation of polyethylene (cellophane) generation and disposal in Akure City, Nigeria was investigated. Five daily markets, were randomly selected for data collection. In each market, two areas: one in the raw food section and the other in the processed food items section, each measuring 30 metres by 100 metres were demarcated for investigation. The result showed that polyethylene is generated more during the dry season months than the wet season months. The result also showed that table water sachet topped the list of cellophane wastes generated. This is because; it is cheap and consumed throughout the year with very little seasonal variation. Types of cellophane generation at home and market also displayed a very interesting pattern. The study showed that in the market, polyethylene for assorted items was the least (51,000), followed by biscuits (50,863), ice cream sachets (81,526) and table water sachets (96,853). On the other hand, the trend showed that, at home, polyethylene for assorted items was the highest (98,361kg), closely followed by biscuit wrapper (45,263), ice cream wrappers (35,514) and table water sachets (25,360). Cellophane waste poses various threats to public health and adversely affects flora and fauna as well as the environment especially when it is not appropriately collected and disposed. It is advocated that aggressive campaign and enlightenment of the masses on the threats posed by cellophane pollution should be carried out to prevent further damage to the environment.